A integralidade da atenção a partir da percepção dos profissionais de uma Unidade Básica de Saúde - Assis Neto, Osorio Queiroga de (2009)
Nowadays, in the public health profile, the integrality is considered as the main fight flag, it can be analyzed as an indicator of direction which must be used in the present system. In this context, since the end of the last century, the challenge of assistance to people who carries HIV has emerged. This challenge must be understood as a complex which involves not only a disease, but also principles which provides properly cares in its work routine. Objectives: In order to improve the access of population to an integral attention concerning health, and the capacity for answering to the principle of integrality, the main purpose of this study is to analyze the integrality practices of attention concerning health from the perceptions of professionals of a Health Basic Unit, and the specific objectives: 1) to digest the conceptions of health among the health professionals; 2) to identify the conceptions of integrality of assistance to health among HBU professionals; 3) to identify the aspects which make difficult or facilitate the guarantee of integrality in the perspective of the Health Professionals; 4) to identify the general competence of the health professionals; 5) to analyze the attention to chronic diseases given by the professionals of HBU, specifically the HIV/Aids; 6) to access the articulation of HBU with the specialized assistance services to HIV/Aids. Method: This study is a descriptive and exploratory field research with professionals of a health basic unit; a quantitative and qualitative approach is used. The sample was composed of 20 workers, representatives of productive medium level and superior level health professional categories, of a Health Basic Unit of the city of João Pessoa PB. Instruments: socio-demographic questionnaire, general competences questionnaire and semi-structured interview. Result Analysis: the bio-demographic and professionals data, as well the General Competence Questionnaire were analyzed through descriptive statistic, using position (Mean, Median) and variability (Standard Deviation, Amplitude) measures. The answers to the open questions were analyzed according to the identified themes, categories and subcategories, based on the methodological resources suggested by Bardin (1979) to the content analysis. Results: Between the more mentioned competences between both groups, it is highlighted the leadership, safety, trusty and humanization, whereas the less mentioned are the creativity with initiative and flexibility, interaction, knowledge of community and health promotion and education, with levels of concordance of 55% to 100%. From the analysis of the interviews, it was highlighted 02 theme classes Integrality in the HBU (with 05 categories: health conceptions among the professionals; conceptions of integrality of assistance concerning health; aspects which facilitate the integrality; aspects which difficult the integrality and improvements to the assistance) and Assistance to Aids (with 04 categories: the perception of professionals of health about Aids; the practice of assistance to Aids; reference and contra-reference system and actions associated to Aids by the health professionals of HBU. Final Considerations: It is acknowledge that in all health general competences observed through the questionnaire, the professionals have difficulties to identify relevant capacities and abilities to the practice of integrality, confirmed by interviews, in which the conceptions about integrality are based on the curative model, requiring the promotion of immediate measures. Thus, there is the necessity pressing of introducing and implementing new bases which can offer necessaries instruments to develop the profession.